Does Piracy Create Online Word of Mouth? An Empirical Analysis in the Movie Industry - Lu, Shijie; Wang, Xin (Shane); Bendle, Neil (Management Science, 2020)
Anecdotal evidence suggests that counterfeiting/piracy can help create online word of mouth (WOM) and through this boost demand, but how powerful is such WOM? To answer this question, we conduct a descriptive study with some attempts to establish near causality. We estimate the impact of piracy on WOM and ultimately revenue by applying a panel data method to all movies widely released in the United States from 2015 to 2017. In identifying the effects of piracy we make inventive use of Russian piracy data to construct instrument variables for piracy in the United States. This is possible because the key piracy site, The Pirate Bay, has been blocked in Russia since 2015. We find movies with prerelease piracy are associated with lower revenues despite the WOM effect. Critically, however, we show a positive correlation between postrelease piracy and WOM volume, and we extend the field by finding that the presence of postrelease piracy is associated with an approximately 3.0% increase in box office revenue. We also note the impact of a raid by the Swedish Police that temporarily took down The Pirate Bay website in December 2014. The period when the site was down experienced a decline in WOM volume and revenues, consistent with the effect of lower postrelease piracy predicted by our models. Our findings suggest approaches to target scarce antipiracy resources, such as focusing on tackling damaging prerelease piracy. This paper was accepted by Juanjuan Zhang, marketing.